Adolescent Health Education in India: Demographic Travails, Contextual Influences and Emerging Health Concerns - Singh, Arun Pratap; Jha, Arbind Kumar (INDIAN EDUCATIONAL REVIEW, 2015)
In view of multiple socio-cultural changes, and rampant rise in exposure and use of information technology in last few decades, the state of adolescent health is marked by several vulnerabilities in different contexts. In order to develop a comprehensive understanding of issues and concerns of adolescent health education, there is a need to build up a framework that gives due recognition to cultural, social and economic contexts of adolescent lives in India. Against this backdrop, the present paper identifies contextual influences and explicates major concerns related to adolescent health education in India.